1985
DOI: 10.1002/tcm.1770050202
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide teratogenesis: A review

Abstract: Cyclophosphamide (CP) is one of the best studied teratogens; it produces primarily central nervous system and skeletal anomalies in rats, mice, rabbits, monkeys, and humans. Furthermore, CP is one of the most extensively studied antineoplastic agents. Recent work using in vitro rodent embryo culture has demonstrated that CP must be bioactivated to be teratogenic. This finding extends earlier work showing that CP must be activated to achieve its antineoplastic and mutagenic effects. Activation of CP to its tera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(102 citation statements)
references
References 41 publications
3
93
0
4
Order By: Relevance
“…Assessment of apoptosis in day 9.0 mouse embryos Vital staining Previous work has shown that cyclophosphamide (Mirkes, 1985a;Mirkes et al, 1991) and hyperthermia (Mirkes, 1985b) induce cell death within the body but not the heart of early postimplantation rat embryos. In this report we extend these findings to early postimplantation mouse embryos exposed to these two teratogens, and in addition, to sodium arsenite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of apoptosis in day 9.0 mouse embryos Vital staining Previous work has shown that cyclophosphamide (Mirkes, 1985a;Mirkes et al, 1991) and hyperthermia (Mirkes, 1985b) induce cell death within the body but not the heart of early postimplantation rat embryos. In this report we extend these findings to early postimplantation mouse embryos exposed to these two teratogens, and in addition, to sodium arsenite.…”
Section: Resultsmentioning
confidence: 99%
“…Like PCD, teratogen-induced cell death is selective, i,e., different cells and tissues within the developing embryo exhibit different sensitivities to the induction of cell death by teratogens. As an example, we and others have shown that neuroectoderm of the early postimplantation rodent embryo is exquisitely sensitive to the cell-death inducing potential of different teratogens, including cyclophosphamide (Mirkes, 1985a;Mirkes et al, 1991), hyperthermia (Mirkes, 1985b), N-acetoxy-2-acetylaminofluorene (Thayer and Mirkes, 1995), cadmium (unpublished data) and deoxyadenosine (Gao et al, 1994). In contrast, the cells of the heart are extremely resistant to the cell death-inducing potential of these teratogens.…”
Section: Introductionmentioning
confidence: 87%
“…Several compounds have been reported to have immunostimulation properties. Cyclophosphamide (CYP) is an alkylating agent widely used as cancer chemotherapy and autoimmune disease therapy [2]. CYP is a well-known and powerful immunosuppressive agent with dosespecific effects.…”
Section: Introductionmentioning
confidence: 99%
“…W badaniach na zwierzętach wykazano wpływ cyklofosfamidu (CYC) na rozwój charakterystycznego zespołu zaburzeń rozwojowych mózgowia, kończyn oraz twarzy [27]. Cyklofosfamid miał nieprzewidywalny wpływ na rozwój płodu ludzkiego, gdyż podawany w I trymestrze ciąży nie zawsze powodował malformacje [28][29][30][31][32].…”
Section: Cyklofosfamidunclassified